Hyperoside suppresses tumor necrosis factor α-mediated vascular inflammatory responses by downregulating mitogen-activated protein kinases and nuclear factor-κB signaling. (1st October 2018) - Jang, Seon-A; Park, Dae Won; Sohn, Eun Hwa; Lee, Sung Ryul; Kang, Se Chan
Abstract: Vascular inflammation has been suggested to play a key role in the initiation and progression of atherosclerosis. Hyperoside (HPS) is a plant-derived quercetin 3-d -galactoside reported to have anti-inflammatory, anti-oxidant, anti-cancer, anti-hyperglycemic, anti-coagulant, and cardioprotective activities. However, the effects of HPS on vascular inflammation have not been studied. Therefore, in this study, we investigated the suppressive effect of HPS on tumor necrosis factor-α (TNFα)-dependent inflammatory responses in MOVAS-1 cells, a murine vascular smooth muscle cell (VSMC) line. HPS did not show any significant cytotoxicity up to 10 μg/mL over 24 h. TNFα challenge of VSMCs significantly increased the mRNA (3-fold) and protein expression (20-fold) of vascular cell adhesion molecule-1 (VCAM-1). However, these increases were abolished in the presence of HPS. Additionally, HPS significantly decreased monocyte adhesion to TNFα–stimulated VSMCs in a dose-dependent manner. Further, TNFα challenge induced activation of mitogen-activated protein kinases (MAPKs), such as p38 MAPK (38.0 ± 3.08 fold), JNK (51.6 ± 2.26 fold), and ERK (14.1 ± 0.77 fold); expression of nuclear factor-κB (NF-κB; ≅ 4-fold) and TNF receptor 1 (TNFR1; 2.7 ± 0.198 fold) were also increased. Notably, the TNFα-induced expression of these molecules was also significantly inhibited by the presence of HPS. Given that p38 MAPK, JNK, ERK, NF-κB, and TNFR1 all play regulatory roles in the expression of VCAM-1, this study provides insight into the mechanism of action of HPS. In summary, HPS can inhibit TNFα-mediated vascular inflammatory responses and has potential as a new anti-atherosclerotic drug. Graphical abstract: Highlights: HPS administration suppresses TNFα-mediated activation of p38, ERK1/2, JNK and NF-κB. HPS downregulates the protein expression level of TNFR1. HPS inhibits the TNFα-mediated increase of VCAM-1 expression in VSMC and thereby suppresses monocyte adhesion to VSMCs.